Effects of Fluorine on the NBTI Reliability and Low-Frequency Noise Characteristics of p-MOSFETs - Sung-Kyu Kwon (IEEE, 2018)
The concurrent effect of fluorine implantation with various energy and dose on reliability and low-frequency noise characteristics of p-MOSFETs was investigated. The $Δ $ VT degradation that represents device lifetime of p-MOSFETs with fluorine implantation under negative-bias temperature instability stress was less than that without fluorine implantation. The device lifetimes were improved as the fluorine implantation energy and dose increase. The power law exponent $n $ with the fluorine implantation was larger than that without fluorine implantation. This was related to boron diffusion within the gate oxide because the F atoms enhance the diffusivity of the boron. The difference of flicker noise levels between simulation and measurement data at 1 kHz was much greater than that at 10 Hz, which means that F atoms were mainly located near the Si/SiO2 interface rather than in the bulk oxide. The fluorine implantation reduced the ID-RTS noise amplitude, which was believed to contribute to the effective passivation of the dominant traps within the gate oxide. Also, the flicker noise was less dependent on implantation energy. But, flicker noise was reduced with increasing implantation dose. Therefore, fluorine implantation is potentially significant for reducing low-frequency noise as well as improving reliability characteristics.